Perubahan Tata Guna Lahan di Sub DAS Rembangan - Jember dan Dampaknya Terhadap Laju Erosi - Idah Andriyani; Sri Wahyuningsih; Siska Suryaningtias (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Inappropriate land use and lack of cover crops may increase erosion rates. The purpose of this study was to compare the erosion rates of land use in Rembangan sub-watershed in 2001 and 2014. The erosion rates were calculated using a USLE (Universal Soil Loss Equation) method. The input data used were rainfall from 2004 to 2014, soil erodibility values based on field measurements, DEM (Digital Elevation Model), and land use maps in 2001 and 2014. USLE modeling showed that erosion rates in the study area in 2001 and 2014 were 873.1 tons/ha/year and 881.9 tons/ha/year, respectively. The erosion rates were classified as a very high level, which covered 42.5% of the total area. So, land conservation action is vital in the Rembangan Sub-watershed.